SISTEM AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA PT. PERTANI (PERSERO) CABANG PEMASARAN SUMATERA UTARA - TRI DHARMA SIPAYUNG (JURNAL ILMIAH KOHESI, 2020)
Cash is the company's cash balance that comes from income that will be deposited to the bank and can be taken at any time in order to finance expenses or company needs. Cash consists of cash accounts and current accounts. Inflows that come and go in the company are called cash flows. The accounting system for cash receipts and disbursements is needed in seeing data of each transaction that occurs within the company. A good company, must have an accounting system that is very useful for the purpose of preventing and maintaining the things that are not wanted, and can also track errors that have occurred and can be corrected. For this reason, cash receipts and disbursement companies are part of what can be said to be very vulnerable to fraud and fraud. That basic basis is required accounting for cash receipts and disbursements can use a good system, namely the organizational structure, procedures, and accounting systems. If the accounting system for cash receipts and disbursements can be implemented as well as possible, then things that can harm the company can be avoided or limited to a minimum.In writing this thesis, the author uses a type of research system of cash receipts and disbursements at PT. PERTANI (Persero) Marketing Branch is one of the State-Owned Enterprises (SOEs) which is engaged in businesses related to the agricultural sector. Data sources used are primary and secondary data. The technique used is descriptive a method in which the data collected are arranged, classified, analyzed so as to produce a clear answer from the problem company. From the results of research conducted by the author concludes the accounting system of cash receipts and disbursements at PT. PERTANI (Persero) North Sumatra Marketing Branch is good, but still has weaknesses, namely the existence of several problems that can be formulated in this case, such as difficulties in processing inventory data where errors often occur in recording data on the same item name, the process of finding data and The delay in presenting sales and inventory reports to the leadership. So companies pay more attention to the accounting system to oversee every part that plays a role in the company.